ANALISA PUBLIC FINANCE MANAGEMENT KABUPATEN MERAUKE - Ida Ayu Purba Riani (Universitas Cenderawasih, 2016)
In the era of regional autonomy, managements in local governments set out accountability and transparency in managing the regional public finance including planning, budgeting, implementation, administering, reporting, accountable and controlling. As from writer’s observation of development performance in Merauke regency, it revealed that there was inadequate development in reaching the ideal development performance although the management was generally well-managed. This paper applied Public Finance Management analysis technique to analyse primary data. The results showed the overall score was 52% from total statements which including 9 sectors. The highest scores were in the planning, cash management, procurement as well as accounting and reporting areas. Key words: Public Finance, Management, Accountability.